GUARANTEES OF RIGHTS AND FREEDOMS OF PEOPLE AND CITIZENS IN THE REPUBLIC OF UZBEKISTAN - Tuxtayev , Azamat Azizovich (Innovative Development in Educational Activities, 2023)
This article delves into the legal framework and mechanisms that safeguard the rights and freedoms of individuals in the Republic of Uzbekistan. It provides an in-depth exploration of the constitutional guarantees, international commitments, and legal instruments that ensure the protection of human rights and civil liberties. The article also highlights notable advancements and ongoing efforts to strengthen these guarantees, making it an informative resource for understanding the legal foundations of human rights in Uzbekistan.